The study of knowledge, attitude and practice of puerperal women about exercise during pregnancy - Esmat Noohi; Mahshid Nazemzadeh; Nozar Nakhei (Iran University of Medical Sciences, 2010)
Background and Aim: Women who engage in exercise programms during their pregnancy have an opportunity to promot physiological and mental health. Current research studies have clearly shown that exercise is not harmful for fetus in healthy pregnancy. The aim of this study was to determine knowledge, attitude and the practice of puerperal women admitted to Kerman hospitals about exercise during pregnancy.   Material and Methods: In this descriptive study after a pilot study, 256 women were chosen by consecutive sampling method. The instrument for data collection was researcher - made 4 parts questionnaire based on theory of planned behavior , consisting of demographic   Characteristic, 23 sentences about knowledge, 11 sentences about attitude and 16 practice sentences about exercise during pregnancy. The validly and reliability was confirmed before using the questionnaire. Information was obtained through face to face interviewing.   Results: The finding showed that the score for knowledge, attitude, and practice was 37%, 72%, and 8% of the total score, respectively. Results also revealed that there was weak positive correlations between knowledge and attitudes (r=0.23), knowledge and practice (r=0.14), and attitude and practice (r=0.26). There was a statistically significant difference between mean score of knowledge of participants in terms of accommodation (p<0.05). Also, there was a statistically significant difference between mean score of attitude of participants in terms of level of education (p<0.01) and spouss's level of education (p<0.01). Results also revealed that there was a statistically significant difference between mean score of practice of participants in terms of level of education (p<0.05), type of delivery (p<0.05) and history of miscarriage (p<0.05).   Conclusion: It seems that mother's concern about exercise during pregnancy is due to their knowledge deficit about permitted exercises during pregnancy. Giving information and education would be helpful to change mothers' knowledg and attitude about the subject, therby, promoting their practice.